The Relationship of Endothelial Dysfunction with the Development of Diastolic Heart Failure in Patients with Hypertension - T. V. Kalinkina; N. V. Lareva; M. V. Chistyakova; V. V. Gorbunov (Столичная издательская компания, 2020)
Aim. To identify genetic predictors of diastolic dysfunction and signs of endothelial dysfunction in relation to indicators of left ventricular myocardial deformity in patients with hypertension.Material and methods. The study included 74 patients (38 women and 36 men) with hypertension 1-2 stages observed in the cardiology department of the Road clinical hospital at Chita II station. The mean age of patients was 32±9.4 years. Circulating endothelial cells (CEC) were determined by flow cytometry with BT 5000 device and antibodies to CD146+, CD45. Besides, 7AAD ion dye was used to detect living and dead endothelial cells. The number of CD146+, CD45 cells per 500000 blood cells was determined. Changes in CEC, Living/Dead CEC were studied. The data was processed using CXP Cytometer and Kaluza programs. The standard echocardiography, Doppler echocardiography and tissue Doppler echocardiography were used. Frequency distribution of alleles and genotypes: 1 mutation nitric oxide synthase 3 gene NOS3 -786 T>C; (С-786Т) in relation to indicators of left ventricular myocardial deformity was analyzed in hypertensive patients with or without diastolic dysfunction as well as in the control group. Polymerase chain reaction with detection of amplification product in real time (RCR-rt) or electrophoresis in agarose gel on genomic DNA of peripheral blood leukocytes were used for studying gene mutations.Results. Development of diastolic dysfunction in hypertensive patients enhanced with the carrier of the genotype NOS3 -786 CC (р=0.01 2, x2=1 2.53), endothelial dysfunction was manifested by an increase in the number of circulating endotheliocytes and was associated with a decrease in global longitudinal deformation of the left ventricle.Conclusion. Endothelial dysfunction in patients with hypertension is associated with a violation of global longitudinal deformation; and in patients with diastolic dysfunction these abnormalities are more pronounced than in patients without diastolic dysfunction.